2012
DOI: 10.1107/s0021889812011715
|View full text |Cite
|
Sign up to set email alerts
|

XDSAPP: a graphical user interface for the convenient processing of diffraction data usingXDS

Abstract: XDSAPP is a Tcl/Tk‐based graphical user interface for the easy and convenient processing of diffraction data sets using XDS. It provides easy access to all XDS functionalities, automates the data processing and generates graphical plots of various data set statistics provided by XDS. By incorporating additional software, further information on certain features of the data set, such as radiation decay during data collection or the presence of pseudo‐translational symmetry and/or twinning, can be obtained. Inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
262
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 287 publications
(264 citation statements)
references
References 20 publications
2
262
0
Order By: Relevance
“…Data were collected at beamline BL14.3 of BESSYII (Berlin, Germany), using a MarMOSAIC 225 CCD detector. The data were processed using XDS (20) as implemented in XDSAPP (21). Data collection and processing statistics are listed in Table 1.…”
Section: Crystallographymentioning
confidence: 99%
“…Data were collected at beamline BL14.3 of BESSYII (Berlin, Germany), using a MarMOSAIC 225 CCD detector. The data were processed using XDS (20) as implemented in XDSAPP (21). Data collection and processing statistics are listed in Table 1.…”
Section: Crystallographymentioning
confidence: 99%
“…a part of the physiological substrate histone H3 and human cathepsin L by crystallizing the complex with a catalytic mutant of the enzyme and elucidating its structure [16]. Refinement confirmed the positioning of only three amino acids from the histone H3 [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] peptide. Our crystal packing analysis suggested that there is not enough space to accommodate all 14 peptide residues in the available space in the active site cleft.…”
Section: Abstract: Cathepsin; Cysteine Cathepsin; Substrate Interactionmentioning
confidence: 99%
“…Crystals appeared within two weeks, were transferred into cryoprotectant (0.1 M MES pH 6.5, 20 mM MnCl 2 , 25 % w/v PEG 8000, 15 % w/v ethylene glycol) and frozen in liquid nitrogen. A 1.95 Å resolution data set was collected at 100 K at BL14.1 operated by the Helmholtz-Zentrum Berlin (HZB) at the BESSY II electron storage ring 37 and processed with XDS 38 and POINTLESS. 39 The crystal showed non-merohedral twinning (twinning fraction α = 0.28) and in addition, non-crystallographic translational symmetry (NCS 50 were acquired with different saturation times (0.5, 1, 2 and 4 s).…”
Section: Methodsmentioning
confidence: 99%